The resilience of Islamic banking efficiency in the face of the Covid-19 epidemic - Faizul Mubarok; Deni Pandu Nugraha; Muhammad Nur Rianto Al Arif (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - Since 2020, the COVID-19 pandemic has harmed the Efficiency Islamic banking industry. This study examines the effects of the COVID-19 pandemic on 33 Islamic stock-traded banks in Asia.Method - This study includes public financial statements and stock prices of Islamic banks in Asia. This study compares peer-to-peer of how the Covid-19 pandemic affect 33 Islamic financial institutions in 2019 and 2020. A dummy-covid separated pre-pandemic and post-pandemic periods and bank efficiency was a dependent variable. Least-squares panel data regression, fixed-effects, and random-effects models determine model parameters.Result - This panel regression analysis shows that Islamic banking's usefulness changed after the Covid-19 pandemic. Islamic financial institutions performed better than usual during the pandemic. The analysis results show this clearly.Implication - Islamic banking appears relatively unaffected by the current economic downturn. The Islamic banking sector, which differs from its conventional counterpart in that it is based on the principle of profit sharing, will fare better during economic contractions, according to these findings.Originality - This is the first study to use a cross-country sample of Islamic banks in Asia to analyze the efficiency of Islamic banking during COVID-19.